Suitability of Missions for the Air Force Reserve Components - Robbert, Albert A. (RAND Corporation, 2014)
The composition of Air Force active and reserve forces is often contentious, especially during a force drawdown. This document seeks to inform force composition decisions by clarifying issues that affect the suitability of missions for assignment to the reserve components.